Spray Pyrolized Pre-coating Layers for Controlled Growth of Zinc Oxide Nanorods by Hydrothermal Process - A. Mahmood, Mohammad; Dutta, Joydeep (Nanoscience & Nanotechnology-Asia, 2011)
Seeding is critical for the hydrothermal synthesis of zinc oxide (ZnO) nanorod arrays on solid substrates. Herein, spray pyrolysis is proposed as a simple and efficient technique for the deposition of ZnO seeding film on glass. The method involves the in situ formation of ZnO nanocrystals by spraying aqueous solution of zinc acetate on hot substrate (°C) whereby ZnO nanocrystallites with narrow size distribution (4-8 nm) are formed. Majority of the crystals were found to have their polar (0001) facet oriented parallel perpendicular to the substrate surface. Upon hydrothermal growth of ZnO nanorods in an equimolar solution of zinc nitrate and hexamine, it was observed that seeding by spray pyrolysis led to the formation of dense ZnO nanorod arrays that were well aligned and strongly attached to the glass substrates.
Keywords: Alignment